Pengaruh Brand Image dan Kualitas Pelayanan terhadap Minat Beli Fore Coffee pada Masyarakat: Survey Masyarakat Jabodetabek - Dea Amelia Putri; Diah Nur Mukholifah; Abdul Yusuf (Economic Reviews Journal, 2024)
The purpose of this study is to determine exactly what the purchase intention of Indonesian consumers in the Jabodetabek area is influenced by the image and service level of the Fore Coffee brand. This study took more than 157 respondents through questionnaires containing students, students, and workers. Because the buying interest of the Indonesian people towards coffee increases every year, it is recorded that the increase in the interest of the Indonesian people increases by 8.8% per year. The results of this quantitative study show that the perception of Fore Coffee's brand image has a major impact on the desire to buy, and good service also influences consumer decisions to buy products. Thus, Fore Coffee can increase buying interest by improving brand image and service quality.